Prompt diagnosis and treatment of cutaneous mucormycosis: a challenging complication in post-renal transplant patients - Singh, Kailash N.; Grover, Ankit; Guleria, Sandeep (International Journal of Research in Medical Sciences, 2025)
A 52 years old male cadaveric renal transplant recipient developed cutaneous mucormycosis, presenting with febrile toxicity and a rapidly growing black lesion. Diagnosis was confirmed by biopsy and treatment began with liposomal amphotericin B. Owing to the high mortality associated with mucormycosis, isavuconazole, a non-nephrotoxic antifungal, was added to Amphotericin B. The patient underwent surgical debridement and his condition subsequently stabilized, accompanied by improved renal function. He was discharged on a combination of isavuconazole and other medications, with good wound healing and a creatinine level of 1.6 mg/dl at one-month follow-up. This case highlights prompt diagnosis and treatment and maintenance with isavuconazole as a viable alternative for mucormycosis in transplant patients with renal impairment.